Integration of Pancasila Student Profile Dimensions in the Independent Learning ECE Curriculum: Narrative Inquiry Early Childhood Education of Teachers Mover in Indonesia - Wahyuningsih, Tri; Rozie, Fachrul; Jafar, Farny Sutriany; Nurhaliza, Tiara; Erawati, Septia Sesia (UPI Kampus Cibiru, 2024)
Integrating the dimensions of the Pancasila student profile in the Independent Learning Curriculum needs to be explored through the experience of driving teachers at the early childhood education level. This research used narrative design inquiry with 6 willing participants from several cities, including Samarinda, Riau, Palembang, Yogyakarta, Semarang and Makassar. Data were collected through indirect observation, documentation studies, and semi-structured interviews, which were analyzed using thematic analysis. The research results showed that the forms of integration of the Pancasila student profile dimensions in ECE units were based on an understanding as a foundation phase, a learning model project based on learning on major and national holiday themes and involving parents. So, we conclude that the experiences of driving teachers can be used as good practice in sharing communities to improve the quality of education. This research also contributes as a sustainable impact to efforts to develop Pancasila learning content at the education level for preschool-aged children to foster the character of loving their homeland, Indonesia.